2021
DOI: 10.1007/s00394-021-02704-y
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of magnesium homeostasis in COVID-19

Abstract: Purpose In less than one and a half year, the COVID-19 pandemic has nearly brought to a collapse our health care and economic systems. The scientific research community has concentrated all possible efforts to understand the pathogenesis of this complex disease, and several groups have recently emphasized recommendations for nutritional support in COVID-19 patients. In this scoping review, we aim at encouraging a deeper appreciation of magnesium in clinical nutrition, in view of the vital role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 93 publications
(101 reference statements)
1
72
2
1
Order By: Relevance
“… 170 , 172 Some authors also consider platelet‐activating factor (PAF) as key in generating microthrombosis in COVID‐19. 12 , 173 PAF has a central role in inflammation due to stimulating the activation of NF‐κB. Furthermore, it has been shown that the reduction of extracellular Mg 2+ results in a rapid increase in active PAF, inducing the NF‐κB activation.…”
Section: Magnesium Consumption During Covid‐19 and Post‐covid‐19 Diseasementioning
confidence: 99%
See 1 more Smart Citation
“… 170 , 172 Some authors also consider platelet‐activating factor (PAF) as key in generating microthrombosis in COVID‐19. 12 , 173 PAF has a central role in inflammation due to stimulating the activation of NF‐κB. Furthermore, it has been shown that the reduction of extracellular Mg 2+ results in a rapid increase in active PAF, inducing the NF‐κB activation.…”
Section: Magnesium Consumption During Covid‐19 and Post‐covid‐19 Diseasementioning
confidence: 99%
“… 5 , 6 , 7 In this sense, magnesium (Mg 2+ ) deficiency causes low‐grade chronic inflammation and OS. 8 , 9 , 10 It has led to the hypothesis that Mg 2+ supplementation might improve the severity of COVID‐19 disease, 11 , 12 including a possible intervention of Mg 2+ in SARS‐CoV‐2 infection by inhibiting the activity of proteases required for protein S cleavage. 12 Therefore, this narrative review focuses on the effect of Mg 2+ to prevent developing severe COVID‐19 from the perspective of Mg 2+ deficiency, which could contribute to an antioxidant/anti‐inflammatory development in COVID‐19 and post‐COVID‐19 manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…First, as previous studies have dicated, the magnesium intake of almost half the population of the United States is un the daily required dose. Thus, more attention should be paid to the increased COVID infection risk among this segment of the population, especially when considering t Since the beginning of the COVID-19 pandemic, the important role of magnesium in the prevention and treatment of COVID-19 has been noted by researchers [3,18,19,22,39]. However, the risks posed by COVID-19 to the magnesium-deficient population require further study.…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune system is the first line of defense in response to pathogens invasion, such as viral infections like COVID-19 ( 38 ). Finally, magnesium regulates the immune system in a variety of ways by orchestrating the activity of immune cells such as neutrophils and macrophages ( 39 ), activating T cells via MagT1 ( 40 ), and regulating vitamin D activity ( 41 ), hence improving the first line of defense in response to pathogens invasion and acting against viral infections like COVID-19 ( 38 ).…”
Section: Discussionmentioning
confidence: 99%